Nghiên cứu hấp phụ anino photphat (PO43-) từ dung dịch bằng oxit hỗn hợp CeO2-Al2O3 - Nhiệm, Đào Ngọc; Hà Chi, Nguyễn Thị; Dũng, Đoàn Trung; Văn, Nguyễn Đức; Lim, Dương Thị (Vietnam Journal of Chemistry, 2016)
The nanostructure mixed oxides powder CeO2–Al2O3 has been synthesized by the combustion of gel from Polyvinyl Alcohol (PVA) as polymer basic and mixture metal nitrate. The optimum conditions of synthesis method: (Ce4++Al3+)/PVA molar ratio = 1/3, Ce4+/Al3+ molar ratio = 1/1, pH = 4, gel formation temperature at 80oC. The phosphate ion sorption of nanostructured CeO2-Al2O3 mixed oxides was presented in this paper. The results showed that the optimized conditions for obtaining the maximum adsorption capacity are: pH 7-9, adsorption equilibrium time of 1h, CeO2/Al2O3 molar ratio of 1/1, calcination temperature of 500 °C, the maximum adsorption capacity, Qmax of 125.42 mg/g with regression coefficient of 0.997 were found. Keywords. CeO2-Al2O3 mixed oxide, phosphate anion (PO43-), anionic adsorption